Peningkatan Kemampuan Numerasi Siswa melalui Media Flashcard pada Materi Bangun Ruang Kelas II SDN 32 Cakranegara - Qolbuani, Lulu Qolbuani; Qomariah, Nur; Nisa, Hairun (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aimed to improve the numeracy skills of second-grade students at SDN 32 Cakranegara on the topic of three-dimensional shapes through the use of flashcard media. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of the study were 24 students. Data were collected through numeracy tests, observation sheets of student activity, and field notes, and were analyzed using descriptive quantitative and qualitative methods. Pre-cycle results showed a learning mastery of 45.83% with an average score of 65.4. In Cycle I, after implementing flashcards, the average score increased to 73.2 with a mastery level of 70.83%, although student engagement reached only 78%. Improvements in Cycle II included adding real-object images to the flashcards and implementing group competition games. As a result, the average score increased to 81.5, learning mastery reached 91.67%, and student engagement rose to 91%. These findings indicate that contextual and interactive flashcards are effective in enhancing students’ understanding of three-dimensional shapes and increasing their engagement. This media is suitable as an alternative teaching tool for mathematics learning in elementary schools.